The Influence of Understanding E-Commerce, Accounting Information Systems, and Business Capital on Decision Making in Entrepreneurship - Salviano, Feby Angelica; Yanthi, Merlyana Dwinda (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study was conducted to examine the influence of e-commerce understanding, AIS, and venture capital on entrepreneurial decision-making. This study was conducted at Surabaya State University. The data collection method used a questionnaire distributed to accounting students. The population in this study was accounting students who had taken or completed the Accounting Information Systems and Entrepreneurship courses or entrepreneurial practices. The data used in this study were primary data obtained from distributing questionnaires to 177 respondents using purposive sampling techniques. Data analysis used multiple regression analysis. The results of this study stated that e-commerce understanding had a positive effect on entrepreneurial decision-making, Accounting Information Systems had a positive effect on entrepreneurial decision-making, and venture capital had a positive effect on entrepreneurial decision-making. Simultaneous testing also indicated that e-commerce understanding, Accounting Information Systems, and venture capital had a significant positive effect, accounting for 51% of the influence of the independent variables on the dependent variable.